Factors Related to the Incidence of Anemia in Pregnant in Women at the Kolaka Health Center and Pomalaa Health Center in Kolaka District - Sri Rahayu Ningsi, Silviani Ardy; Sunarsih, Sunarsih; Nurmiaty, Nurmiaty; Mauliyana, Andi (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community and has a very large influence on the quality of human resources. WHO reports that the prevalence of pregnant women worldwide WHO experience anemia is 41.8%. Method: The type of research used in this study is a quantitative study,namely a cross-sectional study, the research sample size is 98 people obtained by simple random sampling. The data was processed using the chi-square test. Result: This study shows that there is a significant relationship between ANC service quality and anemia in pregnant women with a p-value=0.000. There is a relationship between diet and anemia in pregnant with p-value= 0.009. There is a relationship between adherence to consuming Fe tablets with anemia in pregnant with p-value=0.000. Conclusion: ANC service quality, diet, and Fe consumption compliance have a relationship with the incidence of anemia in pregnant women at the Kolaka Public Health Center and Pomalaa Health Center, Kolaka Regency.